If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4d + -3 + 2d = 9 Reorder the terms: -3 + 4d + 2d = 9 Combine like terms: 4d + 2d = 6d -3 + 6d = 9 Solving -3 + 6d = 9 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 6d = 9 + 3 Combine like terms: -3 + 3 = 0 0 + 6d = 9 + 3 6d = 9 + 3 Combine like terms: 9 + 3 = 12 6d = 12 Divide each side by '6'. d = 2 Simplifying d = 2
| 2x+y=532 | | 1.25+-3= | | 17-s/4-10 | | 9+m=27+27 | | -6(x-2)-26=-14 | | 5*sin(x)+2=sin(x) | | 7n-54=2n+56 | | 5=2+3u | | (-3x+3y)(9x^2+9xy+9y^2)= | | 8+8w+(27+9w)=0 | | 20/25= | | 23x+23=34 | | 3(3x-1)-3(2x)=1 | | 3n+35= | | 0.9x-2.1-0.9=0.2(5-x) | | 0.029x+2=0.034x | | 7(y-6)+3y=10(y+1) | | 11+18=x+19 | | (2/9)g=8 | | 9(4x+1)=10(3x+2) | | 0.029x+2x=0.034x | | 2849=37(p+20) | | f(x)=2t-3whatisf(7) | | -3x+5=-2(3x+5) | | 15+(-5x)=15-5x | | 3y+4=-1y+-4 | | -7u+11=-9(u-1) | | 0.029+2x=0.034x | | 2x(2x-5)(5x+2)=0 | | 8(-9p+2)-7p= | | 814=-22a | | -2(x-7)=-4x+20 |